A publicidade e a retórica do entretenimento - Nakagawa, Regiane Miranda de Oliveira (2007)
This study aims to establish the interaction that advertisements published on magazines have with other semiotic systems. Under this perspective, advertisement pieces are seen as cultural texts and, therefore, they have an informative function in the media environment, which does not restrict only to consume promotion. When we refer to advertisements as texts, we are giving them a very specific form of culture understanding, seen through the different modeling systems that it is made of. This point of view, developed by the Tartu-Moscow School scholars, emphasizes the possibility to observe cultural movement through a dialog between the codes and languages that distinguish the system. Based on analysis of published advertisements on nationwide distributed magazines, two analysis categories were established in this study. They are: concision and redesign. Concision is characterized by limiting elements that make up the text arrangement, whereas redesign starts from an existing original design based on some distinguishing aspects, and then new possibilities of use are presented. Redesign does not disconsider the memory of the already created space because a new configuration comes out from this project. In both cases, it is observed how a dialog with different modeling systems made the rhetoric feature, that distinguishes advertisements, undergo a deep reversion so that, instead of persuading to ratify belief in consume, the advertisements indicate the presence of rhetoric that aims, firstly, to entertain. The presence of this ludic feature, accompanied by the continuous increase of advertisement redesign sign arrangement complexity, explains how advertising may work as media, equally causing support and reviewed media redesign